Resource cell-wireless coverage structure for next-generation ultra-dense networks - Xiayu ZHANG; Jiandong LI; Junyu LIU; Min SHENG; Yan SHI; Ziwen XIE (物联网学报)
With the increasing demand of mobile users for high-speed data transmission services, the problem of insufficient capacity coverage of mobile communication systems in local areas is becoming increasingly prominent.Aiming to eliminate the capacity coverage hole and overcome the complex interference of the network, the resource cell coverage structure was proposed.The coverage structure has the characteristics of elastic scalability and is capable of providing on-demand energy-efficient coverage.Based on the interference management, a basic spatial unit for capacity coverage and energy coverage was formed, and the mutual adaptation of service distribution, energy distribution and coverage structure were realized.Relying on the above coverage structure, a resource cell generation (RCG) method was proposed to enhance capacity coverage.Through dynamically adjusting the coverage structure and providing on-demand network resources, the RCG method could achieve efficient capacity coverage for the uneven service distribution under uniform access point deployment.Simulation and experimental results show that, compared with the traditional static coverage method, the RCG method eliminates the capacity coverage hole, improves the network throughput, and enhances the capacity coverage capability of the network.